An Overview of Innovation Management in Large Companies in Chile, 2010-2019 (GESTIÓN Y TENDENCIAS, 2021)
The aim of this article is to provide an overview of how innovation management capability has evolved within large companies in Chile, describing their behavior over the past decade. The results indicate that at the start of the decade these companies showed some interest in innovation and had sporadic, unsystematic initiatives —maturity Level 1— whereas in the 2015-2019 period companies generally focused on creating value and achieving an impact on their EBITDA, preparing the company for the future —maturity Levels 3 and 4. The lack of systematization in innovation procedures and a lag in developing a culture of innovation are elements requiring substantial improvement in these organizations.
Keywords: innovation management; large companies